High-Throughput Immunogenetics for Clinical and Research Applications in Immunohematology: Potential and Challenges - Langerak, Anton W; Brüggemann, Monika; Davi, Frédéric; Darzentas, Nikos; van Dongen, Jacques J M; Gonzalez, David; Cazzaniga, Gianni; Giudicelli, Véronique; Lefranc, Marie-Paule; Giraud, Mathieu; Macintyre, Elizabeth A; Hummel, Michael; et al. (Journal of immunology (Baltimore, Md., 2017)
Analysis and interpretation of Ig and TCR gene rearrangements in the conventional, low-throughput way have their limitations in terms of resolution, coverage, and biases. With the advent of high-throughput, next-generation sequencing (NGS) technologies, a deeper analysis of Ig and/or TCR (IG/TR) gene rearrangements is now within reach, which impacts on all main applications of IG/TR immunogenetic analysis. To bridge the generation gap from low- to high-throughput analysis, the EuroClonality-NGS Consortium has been formed, with the main objectives to develop, standardize, and validate the entire workflow of IG/TR NGS assays for 1) clonality assessment, 2) minimal residual disease detection, and 3) repertoire analysis. This concerns the preanalytical (sample preparation, target choice), analytical (amplification, NGS), and postanalytical (immunoinformatics) phases. Here we critically discuss pitfalls and challenges of IG/TR NGS methodology and its applications in hemato-oncology and immunology.
Keywords: geny pro imunoglobuliny; Immunogenetics; imunogenetika; High-Throughput Nucleotide Sequencing; výpočetní biologie; genová přestavba; Genes, T-Cell Receptor; Hematology; Genes, Immunoglobulin; geny TcR; lidé; Gene Rearrangement; Humans; vysoce účinné nukleotidové sekvenování; hematologie; Alleles; Immunologic Techniques; imunologické techniky; alely; Computational Biology